Działalność kulturotwórcza i jej rola w bibliotece naukowej na przykładzie Biblioteki Politechniki Lubelskiej - Panasiewicz, Katarzyna; Tomczak, Łukasz (Biblioteka Uniwersytecka w Poznaniu, 2018)
W artykule prezentowane są działania i propozycje upowszechniania kultury realizowane w Bibliotece Politechniki Lubelskiej, dające możliwość rozwoju osobom korzystającym z jej usług i bibliotekarzom. Inicjatywy te uzupełniają i poszerzają ofertę biblioteki oraz stanowią szansę na integrację ze środowiskiem akademickim.

The article presents activities and proposals concerning dissemination of culture carried out in Lublin University of Technology which support the development of the library users and staff. These initiatives complement and extend the library offer as well as provide a chance to integrate with the academic community.
Culture-making activities in research libraries with the example of the Library of Lublin University of Technology
Keywords: Biblioteka Politechniki Lubelskiej; Lublin University of Technology; działalność kulturotwórcza; dissemination of culture; oferta biblioteki; library offer; użytkownicy biblioteki; library users